Effect of COVID-19 in the 2020 MLB Playoffs - Currea, J. (Annual Lyceum Research Showcase, 2021)
Several studies have been performed to explore how the most recent pandemic, COVID-19, has affected the different sports in aspects such as player performance, team performance, player motivation, and franchise performance. In this paper we focus on player and team performance, and how they were affected by this pandemic. In our research, we take into account Sabermetrics which are statistics that measure both individual and collective in-game activity in baseball. Due to the fact that there was a format change for the 2020 MLB Playoffs, in this research, we compare the ALCS, NLCS, and World Series which are 7-game series, and this has not changed since 1994. For this research, we use statistical and analytical topics discussed in our Sports Data Analytics course such as the use of Sabermetrics, and also, some computer science tools such as web scraping in python and data modeling in R. This research is still undergoing; therefore, results will not be posted in the abstract.